2008
DOI: 10.1073/pnas.0801999105
|View full text |Cite
|
Sign up to set email alerts
|

Rapid recurrent processing gates awareness in primary visual cortex

Abstract: Visual awareness has been proposed to depend on recurrent processing in early visual cortex areas including the primary visual cortex (V1). Here, we address this hypothesis with high spatiotemporal resolution magnetoencephalographic recordings in subjects performing a substitution masking paradigm. Neural activity reflecting awareness is assessed by directly comparing the neuromagnetic response elicited by effectively and ineffectively masked targets after the proportion of trials leading to masking was indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
132
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(150 citation statements)
references
References 42 publications
18
132
0
Order By: Relevance
“…Additionally, an fMRI study with the geometrical shape stimuli and a similar subjective visibility scale confirmed that graded perceptual reports from participants reflect genuine intermediate brain states rather than response artefacts (Christensen, Ramsøy, Lund, Madsen, & Rowe, 2006). Several other studies have presented stimuli that are processed early on in the processing hierarchy, and found recurrent processing between posterior brain regions (Boehler, Schoenfeld, Heinze, & Hopf, 2008;Fahrenfort, Scholte, & Lamme, 2008) to be associated with conscious perception. Such findings have led Lamme (2006), Lamme (2010) to develop a graded account of conscious visual perception, which we will call the Recurrent Processing Hypothesis (RPH): higher and lower visual regions engaging in increasing recurrent interactions subtend the gradual increase of awareness of a stimulus, perhaps by promoting increased stability of the corresponding neural activation patterns.…”
Section: Introductionmentioning
confidence: 53%
“…Additionally, an fMRI study with the geometrical shape stimuli and a similar subjective visibility scale confirmed that graded perceptual reports from participants reflect genuine intermediate brain states rather than response artefacts (Christensen, Ramsøy, Lund, Madsen, & Rowe, 2006). Several other studies have presented stimuli that are processed early on in the processing hierarchy, and found recurrent processing between posterior brain regions (Boehler, Schoenfeld, Heinze, & Hopf, 2008;Fahrenfort, Scholte, & Lamme, 2008) to be associated with conscious perception. Such findings have led Lamme (2006), Lamme (2010) to develop a graded account of conscious visual perception, which we will call the Recurrent Processing Hypothesis (RPH): higher and lower visual regions engaging in increasing recurrent interactions subtend the gradual increase of awareness of a stimulus, perhaps by promoting increased stability of the corresponding neural activation patterns.…”
Section: Introductionmentioning
confidence: 53%
“…So far, evidence for the notion that perceptual consciousness arises through recurrent loops of activity between brain areas (Lamme, 2000(Lamme, , 2006 has been primarily limited to studies of vision (Pascual-Leone and Walsh, 2001;Ro et al, 2003;Silvanto et al, 2005;Boehler et al, 2008;Fahrenfort et al, 2008), with an exception of a recent DCM/EEG study in which auditory stimuli were delivered to patients with severe disorders of consciousness (Boly et al, 2011). Our findings allow for a generalization of the recurrent processing hypothesis to the somatosensory modality, suggesting that recurrent activity between regions involved in stimulus processing might be a general mechanism underlying perceptual awareness.…”
Section: Recurrent Processing and Stimulus Detectionmentioning
confidence: 99%
“…Parallel to studies on basic perceptual processes, recurrent processing has gained popularity as a candidate mechanism underlying perceptual consciousness, with evidence ranging from studies using transcranial magnetic stimulation-induced phosphenes (Pascual-Leone and Walsh, 2001), to visual masking (Ro et al, 2003;Boehler et al, 2008;Fahrenfort et al, 2008), motion detection tasks (Silvanto et al, 2005; but see , and effective connectivity analyses in patients with consciousness disorders (Boly et al, 2011). As a result, several influential views on consciousness treat recurrent activity as a condition necessary (Dehaene et al, 2006;Tononi and Koch, 2008) or even sufficient (Lamme, 2000(Lamme, , 2006 for perceptual awareness.…”
Section: Introductionmentioning
confidence: 99%
“…Fronto-parietal networks have also been demonstrated to subserve executive control and working memory (Egner et al, 2008;Bressler and Menon, 2010;Menon, 2013;Rottschy et al, 2012Rottschy et al, , 2013, with prominent activations found in the right hemisphere (Hardwick et al, 2013). Hence, pathologies of these networks or their long-distance connections can critically impair conscious visual perception independently of (van Boxtel et al, 2010;Sumner et al, 2006;Tsuchiya and Koch, 2008;Boehler et al, 2008) or in addition to deficits of attention and central executive networks (Chica et al, 2013). However, the role of fronto-parietal networks for deficient conscious perception, a key symptom in neglect, has remained less well explored.…”
Section: Introductionmentioning
confidence: 99%